Comparison of endotracheal tube cuff inflation techniques by stethoscope and “just seal” method in patients undergoing surgeries under general anesthesia - Rajbhandari, Mona; KC, Nagendra Bahadur; Kunwar, Bhuban Raj; Shah, Bindu Laxmi (Journal of Society of Anesthesiologists of Nepal, 2019)
Background: Overinflation of the endotracheal tube cuff affects tracheal mucosa blood supply that causes postoperative complications like cough, sore throat and hoarseness. There is no standard cuff inflation technique that produces appropriate cuff pressure. The aim of this study was to find out better technique of cuff inflation that will produce adequate pressure with limited complication using stethoscope guided and “just seal”. Methods: This was prospective, randomized single blinded study of 100 American Society of Anesthesiologists Physical Status (ASA PS) I and II patients of 18-65 years undergoing elective surgery under general anesthesia requiring endotracheal intubation. Group J (n=50) received ‘just seal’ method of tracheal cuff inflation where air was introduced into cuff until audible leak at mouth disappeared and Group S (n=50) received stethoscope-guided tracheal cuff inflation where air was introduced into cuff until harsh breath sound changed to soft while listening with stethoscope bell over the thyroid cartilage. Volume of air in endotracheal tube cuff, cuff pressure following inflation and post-operative sore throat, hoarseness and cough at 24 hour were assessed. Results: Demographic details, mean volume of air in cuff, mean cuff pressure and incidence of postoperative adverse effects like sore throat, hoarseness and cough at 24 hours between the groups were comparable. Conclusion: Both the stethoscope guided and “just seal” cuff inflation techniques were equally effective in producing adequate cuff pressure of 20-30 cmH2O with limited complication.